Leveraging halal certification for gastronomy tourism strategy - Fawa’id, Muhamad Wildan; Faiza, Nurlaili Adkhi Rizfa; Abarahan, Amnisuhailah (al-Uqud : Journal of Islamic Economics, 2025)
Gastronomy tourism is one of the fastest-growing sectors in the global travel industry, introducing Muslim tourists to local cuisine prepared with halal ingredients. This study employs a grounded research method—the first and only one to explore the implementation of halal certification—and then applies a SWOT analysis to determine the most effective strategies for supporting halal gastronomy tourism. The findings indicate that the Halal Certification for Original MSME Products in Kediri City (PUSAKA) benefits from strong government support, business owner awareness, and the availability of facilitators to assist with the certification process. However, challenges include limited free certification quotas, administrative constraints, and insufficient capital. Opportunities arise from the growth of halal tourism, national support, and increasing demand for halal products. Meanwhile, threats stem from competition with other regions, potential certification costs in the future, and the risk of inconsistent product quality. To address these challenges, recommended strategies include administrative support, collaborative promotion, and a focus on product quality. The government's approach involves offering free halal certification programs and awareness campaigns to enhance MSMEs' preparedness. Additionally, facilitators provide administrative and technical guidance, while collaboration efforts promote halal-certified products in both domestic and international tourist markets. MSMEs are also encouraged to maintain the quality and consistency of their halal-certified products.